2012
DOI: 10.4038/jnsfsr.v40i4.5042
|View full text |Cite
|
Sign up to set email alerts
|

Replacing traditional half spiral cut by a quarter cut with Ethephon; a simple approach to solve current issues related to latex harvesting in rubber industry

Abstract: Harvesting rubber latex is rather labour intensive since trees are traditionally tapped half spiral, once in two days (S/2 d2) resulting in unnecessary waste of tree bark. High cost of production, shortage of harvesters and reduced economic lifespan are the key issues in rubber plantations related to harvesting. Low intensity harvesting (LIH) systems (i.e. either reduction in harvesting frequency and/or tapping cut length) of rubber appear to be a practical solution to these issues by bringing down the labour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…It is also found in the result that although LFRTS, T 4 and T 5 , consumed the thicker bark shaving per tapping than the other treatments, the total bark consumption of T 4 and T 5 during the study period were apparently lower. It replicates the finding by Rodrigo (2012) that although bark shaving per tapping of LFRTS is thicker than that of the conventional tapping, S/2 d2, the effect is marginal compared to overall bark saving. Vijayakuma et al (2003) reported his finding in India that LFRTS could extend at least four to eight years in the productive lifespan comparing with the conventional tapping system, S/2 d2.…”
Section: Rubber Yield Performancesupporting
confidence: 77%
See 2 more Smart Citations
“…It is also found in the result that although LFRTS, T 4 and T 5 , consumed the thicker bark shaving per tapping than the other treatments, the total bark consumption of T 4 and T 5 during the study period were apparently lower. It replicates the finding by Rodrigo (2012) that although bark shaving per tapping of LFRTS is thicker than that of the conventional tapping, S/2 d2, the effect is marginal compared to overall bark saving. Vijayakuma et al (2003) reported his finding in India that LFRTS could extend at least four to eight years in the productive lifespan comparing with the conventional tapping system, S/2 d2.…”
Section: Rubber Yield Performancesupporting
confidence: 77%
“…Besides, lower bark consumption causes delaying commencement of tapping on renewed barks resulting longer resting period for the renewed bark generation (Kudaligama et al, 2010). Hence, potential higher yield could be expected from the renewed bark under LFRTS (Vijayakumar et al, 2003;Rodrigo et al, 2012).…”
Section: Rubber Yield Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the cost of the application technique and long-term experience (Rodrigo and Kudaligama, 2009), the latter is proven to be the best way to obtain required higher yields associated with reduced lifespan. In general, stimulants are applied with low frequency in tapping which requires less labour hence reduction in the overall cost (Rodrigo et al ., 2012). More importantly, no increase in TPD, instead a decrease, has been recorded where low frequency tapping systems were adopted with ethephon applications (Obouayeba et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A nivel mundial, la explotación del caucho natural basada en sangría de baja intensidad con aplicación de estimulantes a base de etileno (de Faÿ & Jacob, 2018) ha favorecido ampliamente la disminución en los costos de producción y la mano de obra (Rodrigo et al, 2012;Vijayakumar et al, 2001). Por ejemplo, mediante la aplicación del ácido 2-cloroetil fosfónico (etefón), se retrasa el cierre de los vasos laticíferos, pues esto aumenta la permeabilidad de las membranas, prolonga la salida del látex y, por consiguiente, aumenta la producción (Liu, 2016).…”
Section: Introductionunclassified